Analisis Pengaruh Modal Intelektual Terhadap Keunggulan Bersaing - Patria Arsani Putra Arsani; Widyo Nugroho (CV. Publikasi Indonesia, 2020)
The portal of berita-banten.com is an online media under the auspices of PT Fajar Pikiran Rakyat. Launched in 2018, berita-banten.com is a digital media business development unit. The online media beritabanten.com presents news and articles with diverse content, mostly on a regional scale in Banten Province, and nationally and internationally. The purpose of this study is to determine the effect of human capital on Kabar Banten Competitive Advantage, the influence of Structural Capital on Kabar Banten Competitive Advantage, the influence of Customer Capital on the Competitive Advantage of Kabar Banten, and the influence of Human Capital, Structural Capital and Relational Capital simultaneously against the Competitive Advantage Kabar Banten. Based on this research, the results of simultaneous testing (f test) show that together the independent variables have a significant effect on the dependent variable. The result of the partial test (t test) states that the variables of human capital and structural capital and customer capital have a significant effect on competitive advantage.